Introduction to Korea Institute of Oriental Medicine's Korean Medicine Case Report Program - Sungha Kim (MEDrang Inc., 2020)
Several modalities that have been used in Korean medicine have not undergone evaluation. The Korea Institute of Oriental Medicine (KIOM), a South Korean national research agency, launched the Korean medicine case Report (KORE) program in May 2019 to promote case reports, especially among clinicians. The aim was to (1) introduce the KIOM-initiated KORE program, (2) report the results from the KORE program, and (3) present the challenges and limitation from the KORE program. We conducted a narrative review of the cases to which KORE was applied. A total of 16 proposals were reviewed since May 2019. Five proposals were rejected, and 7 case reports were included. Case reports for 3 therapies have been created under guidance. The KORE program makes it easier for Korean medicine doctors to initiate and complete case reports.